The Development of Kriptosistem Polyalphabetic Cipher with Total Antimagic Edges Labeling on Tribune Graph - Muhlisatul Mahmudah (Universitas Islam Jember, 2017)
A graph G of order p and size q is an called an (a,d)-edge antimagic total if there exist a bijection f:(V(G)E(G))? 1,2,...,p+q such that the edge-weights, w(uv) =f(u)+f(v)+f(uv); ; uv,(G) form an arithmetic sequence with ¯first term a and common diference d. Such a graph G is called super if the smallest possible labels appear on the vertices. In this paper we will study a super edge-antimagic total Tribun Graph and the application of developing of polyalphabetic cryptosystem. The result shows that connected Tribun Graph admits a super (a; d)-edge antimagic total labeling for d = 0,1,2, and it can be used to develop a secure polyalphabetic cryptosystem. Keywords: Super (a; d)-edge-antimagic total labeling, Tribun graph polyalphabetic cryptosystem.